2021
DOI: 10.1177/20420188211054692
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of anaplastic thyroid cancer management: perspectives in the era of precision oncology

Abstract: Anaplastic thyroid cancer is a rare aggressive malignancy resulting in poor outcomes, including significant morbidity and mortality. Historically, the overall survival of patients with anaplastic thyroid cancer has been less than 12 months. Multidisciplinary approaches combining surgery, radiation, and chemotherapy have been implemented to control this ominous disease. The evolution in science and technology has promoted deeper knowledge in the genetic pathways and mechanisms driving advance thyroid cancer. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…These findings suggest that there are high gene mutations and abnormal expression of a large number of molecules in ATC, resulting in the imbalance of multiple signaling pathways. 13 , 15 , 18 For drugs through different molecular pathways, see Figure 1 , mechanism and therapeutic efficacy of different drugs are shown in Table 1 . Further randomized clinical trials are also ongoing.…”
Section: Molecular Targeted Drug Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that there are high gene mutations and abnormal expression of a large number of molecules in ATC, resulting in the imbalance of multiple signaling pathways. 13 , 15 , 18 For drugs through different molecular pathways, see Figure 1 , mechanism and therapeutic efficacy of different drugs are shown in Table 1 . Further randomized clinical trials are also ongoing.…”
Section: Molecular Targeted Drug Therapymentioning
confidence: 99%
“…Therefore, in preclinical models, blocking their binding in vitro can enhance the immune response and antitumor activity. 13 , 16 One study revealed the effect of PD-L1 and anti-PD-L1 antibody immunotherapy alone or in combination with BRAF inhibitors on the intratumoral immune response; that is, the combination of PD-L1 antibody and PLX4720 can reduce the tumor volume and increase tumor infiltrating lymphocytes. 37 In addition, the study published by LIN Gui et al reported that a 67-year-old ATC patient had a rapid local recurrence after radical thyroidectomy.…”
Section: Molecular Targeted Drugs Combined With Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of PTC and FTC cases are well-differentiated and patients respond excellently to conventional treatments that include surgery, external beam radiotherapy (EBRT), radio-iodine ( 131 I) and cytotoxic chemotherapies such as paclitaxel 3 5 . However, the outcomes for ATC patients are less favorable as the disease is notoriously difficult to treat 6 . The median survival of ATC patients is less than six months post diagnosis and the 5-year overall survival rate falls below 10% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Worse still, the majority of ATC tumors are radio-iodine refractory and unresponsive to conventional chemotherapies. ATC is a highly mutated disease and several tyrosine-kinase inhibitors (TKIs) are approved for treatment of ATC, including sorafenib (nexavar) and lenvatinib (lenvima) 6 . The former is a multi-kinase inhibitor primarily targeting the vascular endothelial growth factor receptor VEGFR, platelet-derived growth factor receptor (PDGFR) and the Raf-kinases, including c-Raf and b-Raf 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%